Aircraft turnaround and industrial actions: How ground handlers' strikes affect airport airside operational efficiency. (July 2019) - Malandri, Caterina; Mantecchini, Luca; Reis, Vasco
Abstract: The efficiency of airport turnaround operations has often been compromised by various disruptive events out of the airlines' control, such as strikes, which negatively influence the punctuality and regularity of operations. The purpose of this work is to determine the loss of airport operational performance provoked by ground handlers' industrial actions. A discrete-event simulation model of both aircraft landing-and-takeoff (LTO) cycles and turnaround operations has been built by using AnyLogic. If the number of ground handler's operators decreases, turnaround operations require more time to be performed, resulting in delayed departures and knock-on delays. For the case study of Lisbon "Humberto Delgado" airport, turnaround time increases more than linearly with respect to the decrease of staff resources in service. When the number of operators decreases under a certain threshold, turnaround lengthening cannot be absorbed by buffer times and departure delays propagate in cascade over the day. This threshold should call for emergency actions and contingency plans. Highlights: A method to assess ground handlers' strikes' impacts on airport operations is shown A discrete event model is developed reproducing in detail turnaround operations A decreased number of ground operators causes longer turnaround times and delays If on-strike operators exceed a certain threshold, contingency plans may be needed The method is applied to the case of Lisbon "Humberto Delgado" airport